1959
DOI: 10.1071/bt9590034
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of the Bogong High Plains. II. Fencing experiments in grassland C

Abstract: A 10-year fencing experiment in the eroded grassland, type C, of the Bogong High Plains has established the value of the point analysis method for the quantitative study of continuing change in vegetation. The results show that the exclusion of cattle from this widespread type of subalpine grassland results in a gradual improvement in the amount of vegetative cover, especially in that provided by the herb Celmisia. Over the 10-year period there have been striking soil changes in the fenced plot, resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Location of sites mentioned in the text terra australis 32 but the January 2003 fires reversed these gains. The few long-term studies of bog recovery trends in Australia have shown that recovery after fires and grazing takes decades (Carr and Turner 1959;Wahren and Walsh 2000). Sphagnum-shrub bog-with-pool complexes are very slow to recover from disturbance (Ashton and Hargreaves 1993;Good 2000;.…”
Section: Discussionmentioning
confidence: 99%
“…Location of sites mentioned in the text terra australis 32 but the January 2003 fires reversed these gains. The few long-term studies of bog recovery trends in Australia have shown that recovery after fires and grazing takes decades (Carr and Turner 1959;Wahren and Walsh 2000). Sphagnum-shrub bog-with-pool complexes are very slow to recover from disturbance (Ashton and Hargreaves 1993;Good 2000;.…”
Section: Discussionmentioning
confidence: 99%
“…A similar, grazed catchment adjoining the exclosure was to act as a control. Although measurements were made in a range of plant communities between 1947 and 1957 (Carr and Turner 1959;Wahren et al 1994), no data were collected in the peatland communities. The observations of Carr (1977 pp.…”
Section: Introductionmentioning
confidence: 99%
“…was completed in less than one year, and three quarters was completed in five years or less (data not presented). Amongst the longest studies is that established on the Bogong High Plains by John Turner and Masie Carr of the School of Botany at the University of Melbourne, for which observations have been collected now for around 50 years (see Carr, 1977;Carr and Turner, 1959b;Wahren et al, 1994). Notwithstanding the foresight and determination of Carr and Turner, the lack of replication diminishes the robustness of conclusions from this study.…”
Section: Quantitative Analysismentioning
confidence: 86%
“…This was mainly due to the series of research reports on studies in NSW published by Costin and co-workers , that were based on replicated treatments. As is well known, the long-term study plots on the Bogong High Plains in Victoria (Carr and Turner, 1959b) were not replicated. Similarly, only four of the fifteen reported models used replicated data.…”
Section: Quantitative Analysismentioning
confidence: 95%
See 1 more Smart Citation